Recognition of a status acquired abroad: Hungary - Szabados , Tamás (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
In matters related to personal status, the case law of the CJEU and the ECtHR enhances the recognition by states of a status validly acquired or amended abroad. The aforementioned case law has changed and is changing the private international law methodology and practice in national law. This paper analyses how this case law has changed Hungarian private international law, particularly when a legal situation related to the status of the person that has been validly created abroad is sought to be recognised in Hungary
Keywords: personal status; personal law; recognition; legal situation related to the personal status acquired abroad; Hungarian private international law